Comparison of Survival Between Primary Debulking Surgery Versus Neoadjuvant Chemotherapy for Ovarian Cancers in a Personalized Treatment Cohort - Feng, Zheng; Wen, Hao; Li, Ruimin; Liu, Shuai; Fu, Yi; Chen, Xiaojun; Bi, Rui; Ju, Xingzhu; Wu, Xiaohua (Frontiers in Oncology, 2021)
Objective: To compare survival between primary debulking surgery (PDS) and neoadjuvant chemotherapy (NACT) for the treatment of ovarian cancer patients per our selective protocol. Methods: Between Sep 1st, 2015, and Aug 31st, 2017, 161 patients were enrolled in our prospective cohort. All of the patients received preoperative clinic-radiological assessments, according to the Suidan criteria for R0 resection. Patients with a score of 0-2 received PDS. Patients with a score of ≥3 were counseled on the choices of PDS, NACT, or an optional staging laparoscopy, according to the Fagotti criteria. Clinic-pathological data were prospectively collected until May 1st, 2020, and the impacts of different treatment strategies on progression-free survival (PFS) and overall survival (OS) were analyzed. Results: 110 patients underwent PDS, and 51 patients received NACT with consequent interval debulking surgery. The R0 resection rate was 57.8%. All but one of the patients received platinum-based chemotherapy, and 105 (65.2%) patients were platinum-sensitive. Based on the univariate analysis, the PDS group exhibited prolonged PFS compared with the NACT group (P=0.029). The subgroup analysis showed that patients receiving NACT with residual disease (RD) exhibited the worst PFS (P=0.001). Based on the multivariate analysis, NACT with RD was still an independent impaired factor for PFS (P=0.04). However, NACT did not affect OS in the univariate or multivariate analyses. Conclusion: In our prospective cohort, NACT ovarian patients exhibited inferior PFS and noninferior OS compared with PDS patients. Given our selective protocol, NACT cannot be arbitrarily denied while appropriate PDS is still a priority.